2016
DOI: 10.5430/jnep.v6n5p75
|View full text |Cite
|
Sign up to set email alerts
|

Unmet medical care needs in persons with multiple chemical sensitivity: A grounded theory of contested illness

Abstract: We interviewed nineteen persons with self-reported multiple chemical sensitivities in order to explore medical care access and use for this population with a "contested" illness. Interviews were analyzed using grounded theory in the tradition of Glaser, via incident, focused, and theoretical coding. We named the core category health quest (resisting annihilation) and construed four categories that embody the essence of this quest: illness as omnipotent, bidding for access, standard protocols irrelevant, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Koch et al would like rehabilitation counselors to challenge their own biases toward MCS, revise their understanding of universal design, accommodations, and accessibility, and learn to help clients to communicate with their work supervisors and erode their psychosocial isolation. 77 Recently, Gibson et al 78 found, in a grounded theory study, that the core activity of participants, “Healthquest”, was literally a euphemism for “Resisting Annihilation”, given the tremendous obstacles to seeking medical treatment for persons with MCS. In this study, respondents reported wanting their counselors to understand in detail the triggers, symptoms, and lifestyle requirements of those with MCS, to learn some toxicology, to understand how some psychological conditions such as depression and anxiety can be either toxin-induced or secondary reactions to the lifestyle restrictions, to apply the principles of doing good therapy to this population of disabled people, and to make it a priority to provide an accessible office.…”
Section: Discussionmentioning
confidence: 99%
“…Koch et al would like rehabilitation counselors to challenge their own biases toward MCS, revise their understanding of universal design, accommodations, and accessibility, and learn to help clients to communicate with their work supervisors and erode their psychosocial isolation. 77 Recently, Gibson et al 78 found, in a grounded theory study, that the core activity of participants, “Healthquest”, was literally a euphemism for “Resisting Annihilation”, given the tremendous obstacles to seeking medical treatment for persons with MCS. In this study, respondents reported wanting their counselors to understand in detail the triggers, symptoms, and lifestyle requirements of those with MCS, to learn some toxicology, to understand how some psychological conditions such as depression and anxiety can be either toxin-induced or secondary reactions to the lifestyle restrictions, to apply the principles of doing good therapy to this population of disabled people, and to make it a priority to provide an accessible office.…”
Section: Discussionmentioning
confidence: 99%
“…Access is often poor (Gibson, 2010) making it difficult for persons to use the services of physicians, libraries, parks, and even education. Healthcare needs are often unmet (Gibson, Leaf, & Komisarcik, 2016;Gibson, Kovach, & Lupfer, 2015), and even social workers who regularly work with this population have been shown to be unaware of the needs of these clients (Doiron, 2007). disabilities is necessary before system-wide independent living interventions can be developed through centers for independent living, public health departments or other state-wide agencies involved in implementing disability policy" (p. 325).…”
Section: Discussionmentioning
confidence: 99%
“…Existing scientific literature describes aspects of health, social and economic functioning of PEMCS [25][26][27][28][29]. A recurrent theme that emerges is the invisible and complex nature of chemical sensitivities, which makes it difficult to explain to friends or colleagues, and which is often contested by healthcare providers [30]. As a result, PEMCS can be reticent to ask for accommodations for their condition as their symptoms may be trivialized or discounted entirely.…”
Section: Introductionmentioning
confidence: 99%